The spatial suitability evaluation of networked minimarket locations according to Bupati Bantul Regulation No. 35/2013 - Yuri Gama Rivandi; Purnama Budi Santosa (Universitas Gadjah Mada, 2018)
The Regulation of Bupati Bantul Number 35/2013 regulates the establishment of networked minimarket (mini market berjejaring) in Bantul Regency. This study was conducted to assess the suitability between the regulation with the real condition by emphasizing the spatial aspects after 5 years of the implementation of the regulation. This study concerns with the criteria in the regulation about the distance of the mini markets from the traditional markets and the class of the road. The data for cunducting the spatial analysis include road vector data, administrative boundaries, locations of traditional market and networked minimarket, attribute data for networked minimarket, and satellite images of Bantul Regency. The data then was analyzed using proximity and network analysis to know suitability of networked minimarket locations with the regulation. Proximity analysis was done using buffer operation, meanwhile network analysis was done using operation of OD Cost Matrix. Result obtained from the proximity analysis of the overall parameters show that there is only one minimarket in accordance with the regulation. In the other hand, , if the network analysis is included, then the number of minimarkets that comply with the regulation increase to three minimarkets. To conclude, most of the locations of the netwoked minimarkets in Bantul do not comply with the Bupati Bantul Regulation Number 35/2013.